PENINGKATAN KAPASITAS TERMAL PENAMPUNG AIR PANAS SOLAR HEATER MENGGUNAKAN CAPSULATED PARAFFIN - Anggrainy, Rani (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2021)
Solar power is considered as the most essential renewable energy in human life, particularly for daily activities. The application of solar water heater is significantly able to reduce the electric load of water heating so that this method is indirectly able to save energy needs. The biggest challenge is increasing the energy density of warm water storage. The best storage medium is paraffin, but it is constrained by the low thermal conductivity of the paraffin and also the wrapping media. This study focuses on efforts to improve thermal conductivity of paraffin as a heat storage medium by using nickel mixture at a ratio (volume) of 10 - 50%. Samples of paraffin and nickel paraffin mixture are inserted into the wrapper of aluminum 6063 material and then tested for heat absorption and release process. The best heat absorption is shown by the sample with the most nickel content, while in the heat release process the best performing sample is shown with a nickel mixture between 20–40%. These results are directly related to the power rate of each sample. The results of this study can be used as a reference for increasing the thermal capacity of warm water storage from solar water heaters.